Pemberian Discharge Planning dengan Kepuasan Pasien di Ruang Rawat Inap Rumah Sakit Biomedika Mataram - Ageng Abdi Putra; Aprilia Mustika; Eva Marvia; Antoni Eka Fajar Maulana (LPPM STIKES Mataram, 2023)
Introduction: Biomedika hospital is one of private hospitals in Mataram and had applied the program of discharge planning since the beginning of 2017. Data of survey of patients satisfactory in Biomedika Hospital showed that 25% patients felt not satisfied with the service. The data in Biomedika hospital showed that almost 50% of the patients in the one last year are the readmitting old patients. This is why it is necessary to conduct research on this to evaluate the program of discharge planning for the patients satisfactory. Purpuse: The aim of this study is to know about the correlation between providing discharge planning and patients satisfactory. Methods: This research is correlation descriptive study. The sample was selected through cross-sectional method with accidental sampling. Respondents were 78 patients in inpatients wards of Biomedika Hospital. The data were collected through questionnaires to find discharge planning and patients satisfaction. Result: The results of this study showed that there is a correlation between providing discharge planning and patients satisfactory in inpatient wards of Biomedika Hospital proven by the value of p = 0,000 and r= 0,711 which mean there is a strong correlation between providing discharge planning and patients satisfactory in inpatient wards of Biomedika Hospital. Suggestions: It is suggested that health operational procedure made by the hospital